Contextualizing Nariman's God Save the Hon'ble Supreme Court: The Peril of Judicial Subjectivism in Overcriminalization (Tribhuvan University Law Journal, 2025)
The controversy of sitting Leaders of the Supreme Court of Nepal since Gopal Parajuli followed by Deepak Raj Joshi, Sushila Karki, Cholendra Shumsher, Hari Krishna Karki… compel us to ask: ‘have the best times disappeared in the Supreme Court of Nepal or it is again to come! Of them, two of the leaders Sushila Karki and Cholendra Shumsher faced impeachment motion. Nepal Bar Association initiated a movement against Cholendra and a group of former justices summoned a press release for the dignity of the court asking his resignation. Now, Nepal Bar has announced the slogan of ‘restructuring the judiciary’ for its 16th National Conference to be held on Jestha, 2081. The scenario illustrated here does reflect that Supreme Court is not getting the proper leader capable of reforming the judiciary, reforming the appointment in judiciary and managing the dockets of cases pending. The qualification of being the leader of judiciary in Nepal is only the early appointment in SC. Is an early appointment only the quality that the Supreme Court needs in its leader? Is early birth enough to deliver justice? Is Supreme Court getting justice? With these observations, this article tries to contextualize Fali S. Nariman’s God Save the Hon’ble Supreme Court in the setting of Nepal along with its effect conferring into judicial subjectivism and overcriminalization. With the theme: ‘Let Supreme Court get justice, then only the Supreme Court will be able to give the justice!’